HIV status and participation in HIV surveillance in the era of antiretroviral treatment: a study of linked population-based and clinical data in rural South Africa - Bärnighausen, Till; Tanser, Frank; Newell, Marie-Louise (Tropical medicine & international health, 2012)
Objective  To examine whether HIV status affects participation in a population-based longitudinal HIV surveillance in the context of an expanding HIV treatment and care programme in rural South Africa. Method  We regressed consent to participate in the HIV surveillance during the most recent fieldworker visit on HIV status (based on previous surveillance participation or enrolment in pre-antiretroviral treatment (pre-ART) care or ART in the local HIV treatment and care programme), controlling for sex, age and year of the visit (N = 25 940). We then repeated the regression using the same sample but, in one model, stratifying HIV-infected persons into three groups (neither enrolled in pre-ART care nor receiving ART; enrolled in pre-ART care but not receiving ART; receiving ART) and, in another model, additionally stratifying the group enrolled in pre-ART and the group receiving ART into those with CD4 count ≤200/μl (i.e. the ART eligibility threshold at the time) vs. those with CD4 count >200/μl. Results  HIV-infected individuals were significantly less likely to consent to participate in the surveillance than HIV-uninfected individuals [adjusted odds ratio (aOR), 0.74; 95% confidence interval, 0.70-0.79, P < 0.001], controlling for other factors. Persons who were receiving ART were less likely to consent to participate (aOR, 0.75, 0.68-0.84, P < 0.001) than those who had never sought HIV treatment or care (aOR, 0.82, 0.75-0.89, P < 0.001), but more likely to consent than persons enrolled in pre-ART care (aOR 0.62, 0.56-0.69, P < 0.001). Those with CD4 count ≤200/μl were significantly less likely to consent to participate than those with CD4 count >200/μl in both the group enrolled in pre-ART and the group receiving ART. Conclusion  As HIV test results are not made available to participants in the HIV surveillance, our findings agree with the hypothesis that HIV-infected persons are less likely than HIV-uninfected persons to participate in HIV surveillance because they fear the negative consequences of others learning about their HIV infection. Our results further suggest that the increased knowledge of HIV status that accompanies improved ART access can reduce surveillance participation of HIV-infected persons, but that this effect decreases after ART initiation, in particular in successfully treated patients.